Potassium Channels Blockers from the Venom of Androctonus mauretanicus mauretanicus - Marie-France Martin-Eauclaire; Pierre E. Bougis (Journal of Toxicology)
K+ channels selectively transport K+ ions across cell membranes and play a key role in regulating the physiology of excitable and nonexcitable cells. Their activation allows the cell to repolarize after action potential firing and reduces excitability, whereas channel inhibition increases excitability. In eukaryotes, the pharmacology and pore topology of several structural classes of K+ channels have been well characterized in the past two decades. This information has come about through the extensive use of scorpion toxins. We have participated in the isolation and in the characterization of several structurally distinct families of scorpion toxin peptides exhibiting different K+ channel blocking functions. In particular, the venom from the Moroccan scorpion Androctonus mauretanicus mauretanicus provided several high-affinity blockers selective for diverse K+ channels  (SKCa,  Kv4.x, and  Kv1.x K+ channel families). In this paper, we summarize our work on these toxin/channel interactions.